Root growth, infiltration and sand proportion in hass avocado of the colombian andean tropics - Juan Sebastián Arias Garcia; Danielle Fabiola Pereira da Silva; Alejandro Hurtado Salazar; Cristian Agustín Uribe-Castrillón; Cristian Camilo Tabares-Osorio; Nelson Ceballos-Aguirre (Revista Brasileira de Fruticultura)
Abstract: The production of Hass avocados in Colombia has been increasingly threatened by the high and persistent rainfall observed in recent years, which has led to restrictions in root growth, yield reductions, and, in some cases, tree mortality. This study aimed to evaluate the relationship between root growth in Hass avocado trees and the influence of certain soil physical variables in the Colombian Andean tropic. The evaluations were conducted in two commercial 5-year-old Hass avocado plantations, with trees grafted onto rootstocks derived from native seeds. Root growth was assessed through monthly root extractions in each orchard. Additionally, infiltration tests were performed in the drip zones of the trees and along the cultivation paths in each area. Furthermore, laboratory analysis of sand grading was conducted to determine the particle size distribution. Statistical differences in root growth were observed between the two orchards. However, no significant differences were found in drip zone and path infiltration rates or between the overall infiltration rates of the orchards. Root growth was restricted in soils with lower infiltration rates and higher proportion of fine sands.